2015
DOI: 10.1177/0883911515585180
|View full text |Cite
|
Sign up to set email alerts
|

Blends of shellac as nanofiber formulations for wound healing

Abstract: Shellac is being used in food, pharmaceutical, and agricultural industries. It is seldom used for biomedical applications due to its poor mechanical property and instability. We designed thermoresponsive shellac-based bioactive nanofiber mats that mimic extracellular matrix to extend their utility in wound healing. Various blend compositions of shellac, gelatin, and poly(N-isopropylacrylamide) enriched with a bioactive agent, nadifloxacin, were prepared and nanofiber mats were fabricated. The morphology of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Further, the Korsmeyer–Peppas release exponent ( n ) is not uniform for all the formulations, where the formulation F followed anomalous behavior or non-Fickian diffusion, because n is less than 0.5, indicating the rate of solvent diffusion and polymer chain stretching are comparable. 35 So the release of Td was dependent on diffusion of solvent and chain stretching. Meanwhile, the other two formulations followed a Fickian type of diffusion where n < 0.5, so it indicates that the diffusion of solvent was slower than chain stretching due to increased functional interactions between the drug molecules and the polymer chains of the EA.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Further, the Korsmeyer–Peppas release exponent ( n ) is not uniform for all the formulations, where the formulation F followed anomalous behavior or non-Fickian diffusion, because n is less than 0.5, indicating the rate of solvent diffusion and polymer chain stretching are comparable. 35 So the release of Td was dependent on diffusion of solvent and chain stretching. Meanwhile, the other two formulations followed a Fickian type of diffusion where n < 0.5, so it indicates that the diffusion of solvent was slower than chain stretching due to increased functional interactions between the drug molecules and the polymer chains of the EA.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, the −OH, −COOH, and −CHO contained in shellac molecules facilitate the surface modification of shellac nanoparticles, which is of great significance for expanding their drug delivery applications. Shellac nanofibers are another shellac-based nanodelivery system obtained by electrospinning. , Generally, both pure shellac and its mixture with other polymers can achieve excellent applicability for electrospinning applications . Core–shell shellac-based nanofibers can also be fabricated using coaxial electrospinning .…”
Section: Hotspots Deficiencies and Future Perspectivesmentioning
confidence: 99%
“…213 The incorporation of PVP also improves the mechanical properties and drug loading capacity of shellac fibers and increases its dissolution rate through rapid erosion. 72 Vannuruswamy et al 34 found that nanofiber mats formed from a shellac/gelatin/poly(Nisopropylacrylamide) blend had a lower hydrophobicity than shellac nanofiber mats. The blended nanofiber mats achieved 140 h of sustained drug release of drugs with zero-order kinetics.…”
Section: Shellac-based Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was supposed that PVA in aqueous media such as wound exudate would be a fast disintegrated matrix showing a burst release manner, while CA would be a more stable matrix and it was showing a gradual drug release behavior. Tetracycline hydrochloride (TC) as a well-known antibiotic and phenytoin sodium (PHT-Na) as an accelerating drug for cell growth [64][65][66] were loaded into CA and PVA solutions, respectively. Each of polymer solutions (with or without drug) was injected via one syringe placed in opposite directions in an electrospinning apparatus and fibers were collected on an aluminum target.…”
Section: Introductionmentioning
confidence: 99%